Political Leader’s Background Effect on Health Status in Africa: Do Foreign Education Matter? - (:unkn) unknown (My University, 2024)
It is increasingly recognised in the economic literature that political leader is a major actor in the development process of his country. As public resources become scarce against growing needs due to demographic pressure, leaders are faced with the trade-off between development policies. Hence the need to determine the factors motivating their public policy preferences. This paper focuses on the intrinsic motivations, including the leader’s background, in health policy outcomes. In a sample of 31 African countries over the period 1984-2015, for a total of 134 leaders, we show through fixed and random effect, OLS and GCM, Drisc/Kraay and GMM methods that high educated leaders preside over periods of increased life expectancy. However, their place of education, especially foreign western education, confronts them with numerous constraints, making the effect of their stay in the West on the health status of their native country negative. The study contributes to the emerging literature on political leaders theory by providing further evidence that the background of the incumbent political ruler is likely to shape his or her economic policy preferences and hence health outcome.
Keywords: African Research